Proof: Write Skip Line Stack At 2
Let's prove the following theorem:
if the following are true:
- the line at time 2 = 3
- the tab at time 2 = 0
- statement at line 3, tab 1 =
return z
- stack at time 2 = [ ]
then stack at time 3 = [ ]
Proof:
Given
1 | the line at time 2 = 3 |
---|---|
2 | the tab at time 2 = 0 |
3 | statement at line 3, tab 1 = return z |
4 | stack at time 2 = [ ] |
# | Claim | Reason |
---|---|---|
1 | 1 > 0 | 1 > 0 |
2 | stack at time (2 + 1) = stack at time 2 | if the line at time 2 = 3 and the tab at time 2 = 0 and statement at line 3, tab 1 = return z and 1 > 0, then stack at time (2 + 1) = stack at time 2 |
3 | stack at time (2 + 1) = [ ] | if stack at time (2 + 1) = stack at time 2 and stack at time 2 = [ ], then stack at time (2 + 1) = [ ] |
4 | 2 + 1 = 3 | 2 + 1 = 3 |
5 | stack at time (2 + 1) = stack at time 3 | if 2 + 1 = 3, then stack at time (2 + 1) = stack at time 3 |
6 | stack at time 3 = [ ] | if stack at time (2 + 1) = stack at time 3 and stack at time (2 + 1) = [ ], then stack at time 3 = [ ] |
Comments
Please log in to add comments